ЕФЕКТИВНІСТЬ НАВЧАННЯ З ВИКОРИСТАННЯМ ЕЛЕКТРОННИХ ОСВІТНІХ ІГРОВИХ РЕСУРСІВ У ПОЧАТКОВІЙ ШКОЛІ - Bykov, Valeriy Yu; Lytvynova, Svitlana H.; Melnyk, Oksana M. (Information technologies and learning tools, 2017)
The article presents the results of a pedagogical experiment on the study of the effectiveness of education with electronic educational game resources (EEGR) in mathematics, conducted during the experimental work “Rozumnyky” (Smart kids). The obtained results, verified by the mathematical statistics, showed the positive effect of the use of EEGR when studying mathematics on the level of educational achievements, the development of memory and thinking of the experimental group pupils. During the experiment there were positive changes in the pupils’ motivation to study; the number of students perceived EEGR as an assistant during the study increased; those, who got tired or was nervous, if something went wrong when using the resource become less. The promising areas for the future research are the development of EEGR for the integrated training of school subjects in primary school and EEGR for training pupils with special needs, the formation of subject and key competencies with the help of the use of EEGR. В статье представлены результаты педагогического эксперимента по исследованию эффективности обучения с использованием электронных образовательных игровых ресурсов (ЭОИР) по математике, проведенного в рамках опытно-экспериментальной работы «Розумники» (Smart kids). Полученные результаты, проверенные методами математической статистики, свидетельствуют о положительном эффекте обучения с ЭОИР на уровень знаний, развитие памяти и мышления учеников экспериментальной группы. В течение эксперимента произошли позитивные изменения в мотивации к обучению; увеличилось количество учеников, которые воспринимают ЭОИР, как помощника во время обучения; тех, кто устает или нервничает, если что-то не получается при использовании ресурса, стало меньше. Перспективными направлениями исследования являются разработка ЭОИР для интегрированного изучения школьных предметов в начальной школе, а также для учащихся с особыми потребностями, формирование предметных и ключевых компетентностей учеников с помощью использования ЭОИР. У статті представлено результати педагогічного експерименту з дослідження ефективності навчання з використанням електронних освітніх ігрових ресурсів (ЕОІР) з математики, що був проведений у рамках дослідно-експериментальної роботи «Розумники» (Smart kids). Одержані результати, перевірені методами математичної статистики, свідчать про позитивний ефект навчання з ЕОІР на рівень навчальних досягнень, розвиток пам’яті та мислення учнів експериментальної групи. Протягом експерименту відбулися позитивні зміни в мотивації до навчання; збільшилася кількість учнів, які сприймають ЕОІР як помічника під час навчання тих, хто втомлюється чи нервує, якщо щось не виходить під час використання ресурсу, стало менше. Перспективними напрямами дослідження є розроблення ЕОІР для інтегрованого вивчення шкільних предметів у початковій школі, а також для навчання учнів з особливими потребами, формування предметних і ключових компетентностей учнів за допомогою використання ЕОІР.